2011
DOI: 10.2480/agrmet.67.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Spikelet sterility of rice observed in the record hot summer of 2007 and the factors associated with its variation

Abstract: Heat-induced spikelet sterility is one of the major threats to rice production from global warming. Previous chamber experiments have shown that even a short exposure to heat can induce spikelet sterility, but actual damage to a crop in the open field has rarely been reported. In the mid-summer of 2007, the Kanto and Tokai regions in Japan experienced record high temperatures above 40 . We examined whether this extreme heat event induced sterility in open fields. We collected panicle samples from 132 fields in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 17 publications
(22 reference statements)
3
31
0
Order By: Relevance
“…The panicle temperature can be estimated within an agro-meteorology database for rice in Japan (Kuwagwa et al,. Hasegawa et al (2011) field observations in 2007 also showed that the heat-induced sterility was ameliorated by increased nitrogen supply, which conforms to the finding in 2010 of less heat-induced sterility in the field under organic fertilizer management for 11 years (Tanaka et al,. The possibility to ameliorate the heat damage by modifying the nutrient supply warrants further studies to understand the mechanisms.…”
Section: The Findingssupporting
confidence: 86%
“…The panicle temperature can be estimated within an agro-meteorology database for rice in Japan (Kuwagwa et al,. Hasegawa et al (2011) field observations in 2007 also showed that the heat-induced sterility was ameliorated by increased nitrogen supply, which conforms to the finding in 2010 of less heat-induced sterility in the field under organic fertilizer management for 11 years (Tanaka et al,. The possibility to ameliorate the heat damage by modifying the nutrient supply warrants further studies to understand the mechanisms.…”
Section: The Findingssupporting
confidence: 86%
“…In the summer of 2007, the Kanto and Tokai regions of Japan experienced extremely high temperature; for example, the daily maximum air temperature of 40.9 was recorded in mid-August in Kumagaya of Saitama Prefecture in Kanto region and in Tajimi of Gifu Prefecture in Tokai region, which is far higher than the air temperature threshold of HISS according to various chamber experiments. Hasegawa et al (2011) examined the HISS of panicle samples from paddy fields located in Kanto and Tokai regions in 2007 and 2008. The rate of HISS in the hot summer of 2007 was higher than in the normal summer of 2008, and crops whose heading and flowering coincided with the heat wave in mid-August had a higher rate of sterility than crops that flowered earlier or later.…”
Section: Fig 6 Diurnal Variations Of the Effect Of Retarding Of Leamentioning
confidence: 99%
“…The results suggest that global warming will enhance rice production in northern Japan, but reduce production by at least 15-30 % in the southcentral and southwestern parts of the country (Horie et al 1995). In addition, high temperatures during the grain-filling period may reduce rice quality, as measured by grain size, transparency, roundness, and cracking (Yamakawa et al 2007;Morita 2008;Hasegawa et al 2011). However, the way in which high air temperature, especially at night, decreases the fertility of rice grains remains unclear (Cheng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many physiological studies have indicated that decreases in grain size and quality, such as transparency, roundness, and cracking, are caused by abnormal growth of the endosperm under high temperatures (e.g., Morita 2008;Hasegawa et al 2011). For example, rice grain size was shown to decrease when night air temperatures exceeded 21°C during grain filling (Matsushima and Tsunoda 1957;Aimi et al 1959).…”
mentioning
confidence: 99%